Cover Picture: Adsorptive Voltammetry for the Determination of Ochratoxin A Using Enrichment Effect by Cationic Surfactants (Electroanalysis 10/2018). Issue 10 (9th October 2018) - Sultana, Ayesha; Sazawa, Kazuto; Okazaki, Takuya; Islam, Md. Saiful; Hata, Noriko; Sugawara, Kazuharu; Kuramitz, Hideki
Abstract : The cover image illustrates the adsorptive voltammetry for ochratoxin A (OTA) detection using the carbon nanotube paste electrode. It is inspired by the sensitive determination of OTA which can be achieved by adding cationic surfactant, such as zephiramine. The selectivity in this voltammetric detection of OTA can also be further improved by utilizing the specific interaction between OTA and bovine serum albumin. For full text, please see DOI:10.1002/elan.201800226